2017
DOI: 10.1021/acs.est.6b06396
|View full text |Cite
|
Sign up to set email alerts
|

Insight into c-di-GMP Regulation in Anammox Aggregation in Response to Alternating Feed Loadings

Abstract: Substrate concentrations generally fluctuate in wastewaters. However, how anammox biomass behaves to overcome the stress of alternating feed loadings remains unclear. Here, we combined long-term reactor operation, batch tests, 16S rRNA transcript sequencing, and metabolomics analysis to investigate the aggregation of anammox biomass under the regulation of c-di-GMP, a key second messenger, in response to alternating feed loadings. We demonstrated that the aggregation process was significantly faster under alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Metabolic products were extracted from the anammox consortia samples in autotrophic and mixotrophic groups. The protocols used to extract metabolic products were conducted according to those described previously (Guo et al, 2017;Tang et al, 2018b). In brief, anammox consortia suspension was collected by centrifugation, washed using Phosphate buffer saline (PBS), and sonicated using a sonicator.…”
Section: Lc-ms-based Metabolomic Profiling and Quantitation Analysismentioning
confidence: 99%
“…Metabolic products were extracted from the anammox consortia samples in autotrophic and mixotrophic groups. The protocols used to extract metabolic products were conducted according to those described previously (Guo et al, 2017;Tang et al, 2018b). In brief, anammox consortia suspension was collected by centrifugation, washed using Phosphate buffer saline (PBS), and sonicated using a sonicator.…”
Section: Lc-ms-based Metabolomic Profiling and Quantitation Analysismentioning
confidence: 99%
“…Two identical sequencing batch reactors (SBRs) (R-control and R-DSF), with a working volume of 1.0 L were operated for 95 days. Both SBRs were inoculated with 0.29 gVSS L -1 anammox consortia [12].…”
Section: Reactor Operationmentioning
confidence: 99%
“…Previous studies demonstrated that digestive enzymes [7,8], polymeric substances [9], chelating compounds [10], or amino acids [11] could be secreted into extracellular environments as public goods. Extracellular polymeric substances (EPS) are critical for wastewater treatment sludge because of their role in aggregation and biomass tolerance against inhibitors [5,12]. Studies have suggested that amino acid auxotrophy potentially shapes the community composition [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this reaction, SAM supplies the amino group and acyl-ACP provides the acyl group. These molecules are used by Gram-negative bacteria as common signaling molecules and are involved in the regulation of biofilm formation and other properties of the bacteria (Galloway et al 2012; Guo et al 2017). When the concentration of an AHL reaches a threshold as a result of an increase in bacterial cell density, members of the LuxR protein family, which consist of the AHL receptors, would bind to the AHL to regulate the expression of numerous genes involved in various processes, including bioluminescence, pigment and/or antibiotic production, and virulence (Waters and Bassler 2005).…”
Section: Introductionmentioning
confidence: 99%